Unveiling Rural Health Realities: The Case of Gorkha District, Nepal - Devkota, Govinda Prasad; Devkota, Sushila; Khanal, Tantrika Raj (HPE Forum, 2026)
Despite Nepal’s progress in expanding healthcare services, significant healthcare access and quality disparities remain deeply rooted within rural communities such as Gorkha. These inequities extend beyond geographic remoteness, reflecting complex intersections of wealth, education, and social standing. Existing studies often overlook the experiences of frontline healthcare providers who directly confront these challenges. This study examines how doctors and nurses in Gorkha navigate and respond to socioeconomic inequalities in a decentralized health system. Using a qualitative approach, in-depth semi-structured interviews were conducted with 18 healthcare professionals working in both urban centres and remote villages of Gorkha. Thematic analysis was guided by the Social Determinants of Health framework to interpret the data. Four central themes emerged. “The Two Gorkhas” reveals sharp disparities in healthcare shaped by wealth, caste, and education, which eat away at trust in the system. “Adaptive Resilience” shows providers using informal networks and community ties to overcome systemic gaps. “The Double-Edged Sword” highlights how technology both improves service delivery and deepens inequities. “Beyond the White Coat” captures providers’ broader roles in addressing social and environmental health challenges. The study shows that socioeconomic divides more than geography shape healthcare access and trust in rural Nepal. While providers display resilience, lasting progress demands policy reform, stronger local governance, and integrated approaches for equitable and sustainable rural healthcare.